2011
DOI: 10.1016/j.pain.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing racial disparities in pain treatment: The role of empathy and perspective-taking

Abstract: Epidemiological evidence indicates that African Americans receive lower quality pain treatment than European Americans. However, the factors causing these disparities remain unidentified, and solutions to this problem remain elusive. Across three laboratory experiments, we examined the hypotheses that empathy is not only causing pain treatment disparities but that empathy-inducing interventions can reduce these disparities. Undergraduates (Experiments 1 and 2) and nursing professionals (Experiment 3) watched v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(213 citation statements)
references
References 39 publications
8
203
1
1
Order By: Relevance
“…Nurses told to use their best judgment recommended significantly more pain medication for White than Black patients, whereas nurses instructed to imagine how the patient felt recommended equal analgesic treatment regardless of race. 61 It may thus be possible to reduce disparities in pain treatment if providers actively attempt to take patients' perspectives. In addition to behavioral strategies aimed at individual physicians, the contribution of implicit race bias to health care disparities could be reduced on a population level by increasing the number of African American/Black physicians because they consistently demonstrate less race bias.…”
Section: Reducing the Impact Of Implicit Biasmentioning
confidence: 99%
“…Nurses told to use their best judgment recommended significantly more pain medication for White than Black patients, whereas nurses instructed to imagine how the patient felt recommended equal analgesic treatment regardless of race. 61 It may thus be possible to reduce disparities in pain treatment if providers actively attempt to take patients' perspectives. In addition to behavioral strategies aimed at individual physicians, the contribution of implicit race bias to health care disparities could be reduced on a population level by increasing the number of African American/Black physicians because they consistently demonstrate less race bias.…”
Section: Reducing the Impact Of Implicit Biasmentioning
confidence: 99%
“…Arguably, emotional barriers to behaviour change are under-addressed in the work of Michie and colleagues (2005). A good example of targeting emotion to change behavior is that of a successful intervention to boost empathy for ethnic minority patients in pain, thereby improving assessment of their pain, where education on pain had failed to overcome discounting of pain based on racial stereotyping (Drwecki, Moore, Ward & Prkachin, 2011). significant increase in nursing assessment of pain at rest and movement (% not specified) no change in use of nonpharmacological methods…”
Section: The Inclusion Of Neglected Components Of Behavior Change -Inmentioning
confidence: 99%
“…For example, Drwecki et al [66] found that White participants reported greater empathic concern for White individuals in pain than for Black individuals in pain, and ofered higher levels of analgesic treatment for ingroup compared to outgroup members. Also, in two neuroimaging studies, empathy-related neural activity when observing ingroup members' sufering relative to outgroup members' sufering predicted greater willingness to donate time and money [63], as well as greater costly helping [18] for ingroup members at a later stage.…”
Section: Group Membership Empathic Concern and Helping Behaviormentioning
confidence: 99%